EFFECTIVENESS OF IMPLEMENTATION OF INDEPENDENT CURRICULUM IN JUNIOR HIGH SCHOOLS IN DELI SERDANG REGENCY - Amini, Amini; Rahman Dongoran, Faisal; Darma, Surya (UIN Sumatera Utara Medan, 2024)
This study aims to analyze the effectiveness of the implementation of the independent curriculum in junior high schools in Deli Serdang Regency, supporting factors and obstacles that occur in schools. The research method used is mix method research with sequential explanatory designs. Data collection through documentation, observation, questionnaires, and interviews. The collected data was analyzed using data reduction, data presentation, and conclusion drawing techniques. The results of this study indicate that the independent curriculum has been implemented effectively in junior high schools in Deli Serdang Regency, as the results of the questionnaire obtained a very good category, starting from the principal (percentage 84.44%), teachers (percentage 83.92%), and students (percentage 81.95%). Furthermore, this level of effectiveness is reviewed from the optimization of implementation using a transformative learning approach, flexible learning procedures, problem solving through interdisciplinary, meaningful learning, and active student involvement. Supporting factors for the high level of effectiveness of the implementation of the independent curriculum are the high commitment of the school community, learning innovation and teacher creativity, leadership support, and adequate learning facilities. Meanwhile, the obstacles faced are in the form of teachers' abilities in implementing IKM being uneven and there are still teachers who are not yet able to apply sophisticated technology.